Pengaruh Efikasi Diri dan Soft skills terhadap Kesiapan Menjadi Guru Pasca Lantip - Muhammad Za’Faron; Kardiyem Kardiyem (Universitas Negeri Semarang, 2026)
This study aims to analyze the effect of self-efficacy and soft skills on readiness to become a teacher among Accounting Education students post-LANTIP Program. This study applied a quantitative descriptive-explanatory design. Data were gathered through a closed 4-point Likert scale questionnaire administered to 50 respondents. The data were analyzed using multiple linear regression. The findings revealed that: self-efficacy has a positive and significant effect on teacher readines t = 2.712; p = 0.009; soft skills has a positive and significant effect on teacher readines t = 2.321; p = 0.025; and self-efficacy and soft skill simultaneously have a significant effect on teacher readiness, contributing 66.4%. R2 = 0.664. The implications emphasize the need for higher education institutions to optimize microteaching, the LANTIP Program, and soft skills development to enhance the professional readiness of prospective teachers.